Vom Kult zur Marke. Das Nietzsche-Archiv in Weimar und sein Netzwerk. - Fünderich, Maren-Sophie (Artium Quaestiones, 2023)
The Nietzsche Archive in Weimar, which was reorganised by Elisabeth Förster-Nietzsche (1846–1935) after the death of her brother Friedrich Nietzsche (1844–1900), is regarded as an example of an outstanding collection that stands for the dawn of modernity around 1900. The circumstances of how Nietzsche’s sister managed and expanded the archive in Weimar clearly show the structure and development of a network. The archive is located on the ground floor of “Villa Silberblick”, a representative Wilhelminian villa on the outskirts of the city, which Förster-Nietzsche had moved into in 1897, and where she cared for her brother and where she remained after his death. This collection in the Nietzsche Archive includes furniture and interiors that Förster-Nietzsche had commissioned from the up-and-coming Belgian architect Henry van de Velde (1863–1957). She wanted to create a place for the Nietzsche cult, which she pursued with all her might, and to have her brother’s works translated into interior design. She was helped in this by patron Harry Graf Kessler (1868–1937), who was looking for a reference project in Weimar for Van de Velde, the new artistic advisor to the young Grand Duke of Saxe-Weimar, and recommended him to Förster-Nietzsche. With Van de Velde’s establishment, the Nietzsche Archive became not only a focal point of Nietzsche worship at the beginning of the 20th century, but also the centre of the “New Weimar”, a cultural-political project for which Kessler and Förster-Nietzsche were able to gain the support